2013
DOI: 10.1631/jzus.a1300242
|View full text |Cite
|
Sign up to set email alerts
|

Development of a system configuration for a solar powered hydrogen facility using fuzzy logic control

Abstract: Solar energy is a natural resource which can be harnessed to provide clean electricity for hydrogen production systems. However, this technology is not widely used because of control issues, particularly for hydrogen refuelling stations. At present, direct or DC-DC converter couplings are the most common system configurations for hydrogen refuelling stations. However, these system configurations are costly and suffer from gas shortage at hydrogen refuelling stations. Furthermore, the hydrogen produced by such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It should be noted that the optimal PV-electrolyzer power ratio depends on several effects, e.g., the cost of energy units, the energy available from RES, the hydrogen demand profiles. Castellanos et al [13] identified an optimum power ratio between the PV and electrolyzer of 2.85, while in [14], the optimum power ratio was about equal to one.…”
Section: Of 14mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the optimal PV-electrolyzer power ratio depends on several effects, e.g., the cost of energy units, the energy available from RES, the hydrogen demand profiles. Castellanos et al [13] identified an optimum power ratio between the PV and electrolyzer of 2.85, while in [14], the optimum power ratio was about equal to one.…”
Section: Of 14mentioning
confidence: 99%
“…Other studies addressed the preliminary design and optimization of green hydrogen energy systems with reference to both techno-economic and environmental aspects. For example, the studies proposed in [13,14] analyzed multi-energy systems and determined the photovoltaic (PV)-electrolyzer power ratio, which minimized the green hydrogen production cost. It should be noted that the optimal PV-electrolyzer power ratio depends on several effects, e.g., the cost of energy units, the energy available from RES, the hydrogen demand profiles.…”
Section: Of 14mentioning
confidence: 99%